Assessment of Traffic Safety Among Young People Aged 15 to 24 in Slovenia - Zanne, Marina; Groznik, Aleš; Twrdy, Elen (Promet - Traffic&Transportation, 2013)
The probability that an individual will be involved in a car accident is relatively high. Traffic safety is a global problem, and Slovenia is no exception. Despite the large improvement in traffic safety records, Slovenia still ranks very low on the European level with 63 fatalities per million inhabitants. The paper analyses the official data on traffic accidents in Slovenia in the period from 1999 to 2011. The paper presents an overview of road safety in Slovenia with emphasis on the participation of young people in severe accidents. It has been examined whether young people in Slovenia are the most dangerous and at the same time the most vulnerable category of road users and the causes of road accidents involving young people have been compared with the causes of accidents involving overall population.